Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.cogc.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Concurrent Chemoradiation in Cervical Cancer Patients From Rural Background

Abstract: There is paucity of literature about tolerability of standard chemoradiation in cervical cancer patients of rural background; hence, we undertook this study. Enteritis and dyselectrolytemias were the most common toxicities and the key reasons for radiation interruption and suboptimal chemotherapy doses. Nutritional and social support along with vigorous assessment for dyselectrolytemias and timely management is the key to optimizing treatment. Background: Concurrent chemoradiation causes toxicities such as ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Our data also showed no correlation between distance from the cancer centre and RNC utilization. Another study has shown that patients from rural backgrounds receiving CCR for cancer of the cervix experience greater acute toxicities [ 35 ]. Given that nearly all patients in our study lived within 100 km of the cancer centre, which is a large tertiary care centre, we may be under-representing this vulnerable population in our study; future work is recommended to identify their supportive care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed no correlation between distance from the cancer centre and RNC utilization. Another study has shown that patients from rural backgrounds receiving CCR for cancer of the cervix experience greater acute toxicities [ 35 ]. Given that nearly all patients in our study lived within 100 km of the cancer centre, which is a large tertiary care centre, we may be under-representing this vulnerable population in our study; future work is recommended to identify their supportive care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Poor compliance and enhanced acute toxicity are reported in patients from a rural and underprivileged background in LMICs [34]. Audits from developing countries report 42e85% compliance to planned chemoradiation schedules, with a substantial majority of patients receiving less than five cycles of concurrent chemotherapy [29,35,36].…”
Section: Access and Delivery Of Concurrent Chemotherapy For Cervical mentioning
confidence: 99%
“… 33 Another study from rural India reported poor compliance, higher grade III toxicity, and treatment breaks. 44 Up to 16% to 20% of patients had treatment gaps as a result of toxicity and received three or fewer cycles, which reduced the cumulative dose to 152 mg/m 2 (80 to 200 mg/m 2 ) rather than the desired cisplatin dose of 225 to 250 mg/m 2 . 33 , 45 In patients with coexisting HIV infection, potential interactions between antiretroviral drugs and cancer therapy should be considered, and higher toxicity and poor outcomes 46 may be anticipated.…”
Section: Managementmentioning
confidence: 99%